(untitled) (International Journal of Engineering and Computer Science, 2025)
The telecommunications industry is undergoing a significant transformation fueled by 5G, edge computing, and the adoption of cloud-native technologies. As telco workloads increasingly shift to private cloud environments, the role of storage becomes critical in ensuring performance, scalability, and reliability. From 5G core functions to real-time edge processing, telco applications demand high IOPS, low latency, and continuous availability—requirements that challenge traditional storage systems. This paper explores the capabilities of modern container storage solutions like Red Hat ODF (Ceph), Portworx, and Dell CSM, analyzing how they meet the stringent demands of telco workloads. By examining real-world scenarios, performance benchmarks, and operational behavior under stress, we offer guidance on selecting storage architectures that enable resilient, secure, and agile service delivery across centralized and edge deployments in private cloud infrastructures.